BiOBr hybrids for organic pollutant removal by the combined treatments of adsorption and photocatalysis. Issue 56 (18th September 2018) - Yu, Yichang; Li, Chengjun; Huang, Shoushuang; Hu, Zhangjun; Chen, Zhiwen; Gao, Hongwen
Abstract : The x SiO2 –BiOBr ( x = 0–5) and SN–SiO2 –BiOBr hybrids were synthesized via a facile one step co-precipitation method. Abstract : The x SiO2 –BiOBr ( x = 0–5) and SN–SiO2 –BiOBr hybrids were synthesized via a facile one step co-precipitation method. To determine the optimal formula, the photocatalytic degradation of C. I. reactive red 2 (X3B) with x SiO2 –BiOBr ( x = 0–5) was investigated. Under simulated sunlight irradiation, 4SiO2 –BiOBr exhibited a better photocatalytic efficiency than other materials; 1.77 and 1.51 times higher than conventional nano TiO2 and pure BiOBr, respectively. To demonstrate the photocatalytic degradation mechanism, the effect of active species on degradation of X3B was carried out, and a possible degradation pathway was proposed. To realize the combined treatments of adsorption and photocatalysis, an inorganic/organic (I/O) SN–SiO2 –BiOBr hybrid was further strategized and synthesized. It showed much better adsorption performance than the SiO2 –BiOBr composite. It could enrich organic pollutants by facile adsorption, and then degrade them to H2 O and CO2 under natural sunlight irradiation. Notably, this sunlight-driven photocatalysis can be performed in the slurry resulted from the pollutant adsorption. As a result, the proposed combination of adsorption and photocatalysis will provide a novel strategy to greatly facilitate the treatment of organic wastewater.